European Organization for Caries Research Workshop - Methodology for Determination of Potentially Available Fluoride in Toothpastes - Martinez-Mier, E. Angeles; Plett, Walter; Fluoride in Toothpaste Analysis Work Group, Orca (Caries research, 2019)
Toothpastes are the most universally accepted form of fluoride delivery for caries prevention. To provide anti-caries benefits, they must be able to release fluoride during the time of tooth brushing or post brushing into the oral cavity. However, there is no standard accepted procedure to measure how much fluoride in a toothpaste may be (bio) available for release. The European Organization for Caries Research proposed and supported a workshop with experts in fluoride analysis in toothpastes and representatives from industry. The objective of the workshop was to discuss issues surrounding fluoride analysis in toothpaste and reach consensus on terminology and best practices, wherever the available evidence allowed it. Participants received a background paper and heard presentations followed by structured discussion to define the problem. The group also reviewed evidence on the validity, reliability and feasibility of each technique (namely chromatography and fluoride electroanalysis) and discussed their strengths and limitations. Participants were able to reach a consensus on terminology and were also able to identify and summarize the advantages and disadvantages of each technique. However, they agreed that most currently available methods were developed for regulatory agencies several decades ago, utilizing the best available data from clinical trials then, but require to be updated. They also agreed that although significant advances to our understanding of the mechanism of action of fluoride in toothpaste have been achieved over the past 4 decades, this clearly is an extraordinarily complex subject and more work remains to be done.